2021
DOI: 10.1186/s12903-021-01739-1
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of root morphology and canal configuration of maxillary premolars in a Saudi subpopulation: a cone-beam computed tomographic study

Abstract: Background The objective of this study was to use CBCT to look into the root canal morphology of maxillary premolars in a Saudi Arabian subpopulation and associate the results to existing canal morphology classifications. Methods The sample size for this analysis was 500 right and left untreated maxillary first and second premolars with fully formed roots from 250 Saudi residents (125 male and 125 female). The following observations were made using… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 68 publications
(79 reference statements)
4
13
0
1
Order By: Relevance
“…A high percentage of root morphology was two roots, followed by one root and three roots. Similar results were found in previous studies conducted in Saudi Arabian subpopulations, Jordanian population, and Turkish populations, which also observed a higher prevalence of two roots followed by one root than three roots [19,28,[37][38][39][40]. Some studies showed results that were near to our findings regarding the prevalence of the number of roots with a slight variation in the percentage of the number of roots, like the studies that have been conducted in Saudi, North America, Andalusia, Singapore, Turkey, Poland, Ugandan, San Sebastian, southern India, and Australia population [5,17,21,[41][42][43][44][45][46][47][48]..On the contrary, studies in the Shandong Chinese population showed a higher prevalence of one-rooted than two-rooted maxillary first premolar [6,49].…”
Section: Discussionsupporting
confidence: 91%
“…A high percentage of root morphology was two roots, followed by one root and three roots. Similar results were found in previous studies conducted in Saudi Arabian subpopulations, Jordanian population, and Turkish populations, which also observed a higher prevalence of two roots followed by one root than three roots [19,28,[37][38][39][40]. Some studies showed results that were near to our findings regarding the prevalence of the number of roots with a slight variation in the percentage of the number of roots, like the studies that have been conducted in Saudi, North America, Andalusia, Singapore, Turkey, Poland, Ugandan, San Sebastian, southern India, and Australia population [5,17,21,[41][42][43][44][45][46][47][48]..On the contrary, studies in the Shandong Chinese population showed a higher prevalence of one-rooted than two-rooted maxillary first premolar [6,49].…”
Section: Discussionsupporting
confidence: 91%
“…These findings are consistent with other studies conducted in Saudi and Pakistani populations to evaluate the root canal anatomy of premolars. These previous studies also reported that most maxillary first premolars possess two roots, whereas the majority of maxillary second premolars and mandibular premolars have single roots [34,35]. A study comparing numbers of roots and root canal configurations between Asian and White ethnic groups reported contradictory results, indicating that in the Asian group 83.2% of maxillary first premolars exhibited a single root, while in the White group, the prevalence of single-rooted maxillary first premolars was 48.7% [36].…”
Section: Discussionmentioning
confidence: 98%
“…The clinical efficiency of endodontic treatment procedures is dependent on a comprehensive knowledge of root structure and variance probability in root canal configuration, as undetected root canals lead to a treatment failure [ 30 ]. The present study demonstrated the root structure and root canal configuration of maxillary and mandibular first molars by using CBCT and its association with gender in the Saudi population.…”
Section: Discussionmentioning
confidence: 99%